Molecular Approaches to Protein Dimerization: Opportunities for Supramolecular Chemistry - Dang, Dung Thanh (Frontiers in Chemistry, 2022)
Protein dimerization plays a key role in many biological processes. Most cellular events such as enzyme activation, transcriptional cofactor recruitment, signal transduction, and even pathogenic pathways are significantly regulated via protein-protein interactions. Understanding and controlling the molecular mechanisms that regulate protein dimerization is crucial for biomedical applications. The limitations of engineered protein dimerization provide an opportunity for molecular chemistry to induce dimerization of protein in biological events. In this review, molecular control over dimerization of protein and activation in this respect are discussed. The well known molecule glue-based approaches to induced protein dimerization provide powerful tools to modulate the functionality of dimerized proteins and are shortly highlighted. Subsequently metal ion, nucleic acid and host-guest chemistry are brought forward as novel approaches for orthogonal control over dimerization of protein. The specific focus of the review will be on host-guest systems as novel, robust and versatile supramolecular approaches to modulate the dimerization of proteins, using functional proteins as model systems.